Response of Mineral Constituents and Storability of the Postharvest Mango (Mangifera indica L.) to Different Storage Treatments - Islam, MK (Journal of Environmental Science and Natural Resources, 2015)
Efficacy of storage treatments, namely control, paraffin coating, perforated polyethylene cover, unperforated polyethylene cover, hot water (55±1 0C) and low temperature (4±1 0C) on behavioral pattern of mineral constituents and storability of the two postharvest mango genotypes (viz., Langra and Khirshapat) was examined in the sophisticated laboratory of SRDI, Rajshahi, Bangladesh during the period from June, 2011 to September, 2012. The results of the investigation obtained from genotypes appeared predominant variation in terms of most of the characters studied in the laboratory situation. The Langra enriched a greater amount of P, Mg, Fe and Mn over the Khirshapat and the process of enrichment was gradually increased with the advance of storage period up to the last edible stage. The Khirshapat showed a greater performance in producing of Ca, Cu and Zn, and longer shelf life in comparison with the Langra at all the storage times. The mineral constituents of mango pulp were also changed during storage period. Low temperature (4±1 0C) was found to be more effective in retaining the original green color of mangos for a period of time, but it caused chilling injury and fruits did not ripen at all after removal from low temperature. Paraffin coating was assumed to be better in retarding the ripening process of the postharvest mango, which might be easily adopted by common people for the mango storage. DOI: http://dx.doi.org/10.3329/jesnr.v6i1.22043 J. Environ. Sci. & Natural Resources, 6(1): 69-77 2013